Prevalence of tattooing and knowledge about health risk associated with it among adolescent school students in Manipur, North-eastern India: a cross-sectional study - Oinam, Joymati; Singh, Akoijam Brogen; Singh, Yumnam Ningthemba (International Journal Of Community Medicine And Public Health, 2019)
Background: Tattooing has emerged as common activity among adolescents. Therefore, it is important to informed adolescents about possible health hazards associated with it. The objective of the study was to determine the prevalence of tattooing and knowledge of health risks associated with it among higher secondary students and association between knowledge on risk factors with selected socio-demographic variables. Methods: A cross-sectional study was conducted from September to October 2015 among 1325 students studying in class XI and XII in Thoubal district of Manipur in Northeast India. A self-administered questionnaire was used for data collection. Based on the obtained score, knowledge was divided into adequate and inadequate. Descriptive statistics like mean (SD) and percentages were used. Chi-square test was used for testing the significance and p<0.05 was considered as statistically significant. Results: Total of 1378 students participated in the study. Almost all the students (99.5%) have heard of tattoo but only 75 of them (5.5%) had ever tattooed. Majority (87%) of the students had inadequate knowledge. Ever tattooed was more among male students compared to female. There was significant association between adequate knowledge and male students, parents who had secondary and above education. Significant association was found among those who had adequate knowledge and risk of transmission of disease through tattooing. Conclusions: Prevalence of ever tattooed was 5.5%. Though majority of the participants had heard of tattoo but most of them had inadequate knowledge about health risk associated with tattooing.